Policy Knowledge Gap Among Senior Citizens (Pragyaratna प्रज्ञारत्न, 2024)
The Nepalese government provides various allowances, including old age, widow, disability, and nutritional grants, to improve the quality of life for economically and socially disadvantaged individuals. This study assesses the relationship between knowledge on old age allowance policy/facility and their Quality of Life (QOL) among senior citizens of Biratnagar, a metropolitan city of Morang district. The study used a cross-sectional survey design to measure the current status of senior citizens in Biratnagar, a metropolitan city, and identify their quality of life. Independent variables like knowledge on Old Age Allowance (OAA) public transportation concession and seat preservation, government waiver on treatment fees free health service for 75+ patients, government's social security/welfare policy, spend the allowance, and opinion on current old age allowance were quantified. The sample size was calculated using Raosoft online calculator, with 370 senior citizens selected. The study in Biratnagar investigated senior citizens' quality of life using WHOQOL-BREF questionnaire and interview, establishing a link between quality of life and old age allowance. The paper examined the quality of life (QOL) of senior citizens in Biratnagar, focusing on policy factors. Most of the seniors received old age allowance and used government facilities. However, a significant percentage was ignorant of the policy, resulting in poor QOL. The majority of respondents reported using facilities provided by government offices and hospitals, but there was a lack of knowledge about related policies. The study would be beneficial to have the positive impact so that the concerned stakeholders would initiate on the policies and old age allowance (OAA) on senior citizens' quality of life.